A year after Crimea: continuity and change of Finnish-Russian relations reflected in the views of the government officials of Finland and Russia - Karlova, Marina (My University, 2016)
This thesis discusses the dynamism of bilateral relations between Finland and Russia and their interconnection with wider EU-Russia relations in the sight of the recent conflict in Ukraine. In particular, incorporation of Crimea in the territory of Russia in March 2014 is believed to have triggered a series of disputes between the European Union and Russia and thus, have impacted the course of the bilateral Finnish-Russian relations. The study leans on a premise that there are some historical traditions and regularities in the Finnish foreign policy course towards Russia which make the bilateral Finnish-Russian relations special. These traditions are distinguished and described in the book “Russia Forever? Towards Pragmatism in Finnish/Russian relations” (2008) edited by H. Rytövuori-Apunen. Assuming that the featured traditions take place in modern relations between Finland and Russia, the aim of the thesis is to find out how these traditions reappear during the year shaped by the events in Ukraine. In order to do that, author follows the timeline of happenings around the Ukraine crisis starting with Crimea’s referendum on independence, and exams the way these events were commented on and evaluated by the key government officials and political institutions of Finland and Russia. The main focus is given to the Finnish official discourse on Russia during the study period. The data collection, consisting of mostly primary sources (ministerial press releases and comments, statements, speeches and blog posts of individual policy makers) is processed using the thematic analysis supported by the content analysis. The study reveals that the consequences of the Ukraine crisis have brought, among others, complications to the economic cooperation between Finland and Russia, and have stimulated the increased attention of the Finnish decision makers to the country’s security questions. As a result, the character and importance of some historical regularities of the Finnish foreign policies on Russia, like the Continental Dilemma, have taken new shape.